Pin1-dependent signalling negatively affects GABAergic transmission by modulating neuroligin2/gephyrin interaction - Antonelli, Roberta (Nature Pub. Group, 2014)
The cell adhesion molecule Neuroligin2 (NL2) is localized selectively at GABAergic synapses, where it interacts with the scaffolding protein gephyrin in the post-synaptic density. However, the role of this interaction for formation and plasticity of GABAergic synapses is unclear. Here, we demonstrate that endogenous NL2 undergoes proline-directed phosphorylation at its unique S714-P consensus site, leading to the recruitment of the peptidyl-prolyl cis–trans isomerase Pin1. This signalling cascade negatively regulates NL2’s ability to interact with gephyrin at GABAergic post-synaptic sites. As a consequence, enhanced accumulation of NL2, gephyrin and GABA(A) receptors was detected at GABAergic synapses in the hippocampus of Pin1-knockout mice (Pin1−/−) associated with an increase in amplitude of spontaneous GABA(A)-mediated post-synaptic currents. Our results suggest that Pin1-dependent signalling represents a mechanism to modulate GABAergic transmission by regulating NL2/gephyrin interaction.